Cannabis policy and the burden of proof: Is it now beyond reasonable doubt that cannabis prohibition is not working? - Lenton, Simon (2000)
'Innocent until proven guilty' is how many policy makers have thought about the prohibition of cannabis in Western Australia and elsewhere. Comparisons between so called 'decriminalized' and prohibitionist states show decriminalization has not led to higher rates of current cannabis use. Under prohibition significant numbers of Western Australian citizens receive a criminal record for no more serious offence than the possession of a small amount of cannabis for personal use. Recent research has shown that such a conviction can have a real and detrimental impact on people's lives, reinforces disrespect for the cannabis laws, but appears not to deter cannabis use among those so convicted. This paper suggests that it is now beyond reasonable doubt that applying criminal sanctions for minor cannabis offences is not in the best interests of the community and recommends an alternative.